Atomic commit protocols, their integration, and their optimisations in distributed database systems. (1st October 2010) - Al-Houmaily, Yousef J.
Advanced software application systems commonly execute atop multiple interconnected computing platforms. Regardless of whether the underlying platforms being homogeneous or heterogeneous, such systems require basic reliability guarantees to ensure deterministic outcomes in the presence of faults. Similar guarantees are provided by database systems through the 'atomicity' property of transactions. In distributed database systems, this property is ensured, across different database sites, by means of 'atomic commit protocols' (ACPs). An ACP guarantees, in spite of possible failures, that each transaction has a deterministic final outcome. This outcome represents either the execution of the transaction as a whole, across all participating sites, or none at all. Thus, it is imperative to trace the problem of atomic commitment in distributed database systems and to highlight its current dimensions as well as its proposed solutions. Such an effort establishes a foundational stage for investigating and developing more elaborate and novel solutions to the problem. These solutions are likely to satisfy the reliability needs of future generations' application systems in a cost-effective manner.